Electrification of Inland Waterway Ships Considering Power System Lifetime Emissions and Costs - Maja Perčić (MDPI AG, 2021)
This paper deals with the applicability of alternative power system configurations to reduce the environmental footprint of inland waterway ships. Its original contribution includes: models for assessment of the lifetime emissions and associated lifetime costs of alternative power system configurations for different types of inland waterway vessels, identification of the most cost-effective options for these vessels, and an estimation of the impact of emission policies on the profitability of each option. The case study considers the Croatian inland waterway sector, where three types of vessel with significantly different purposes, designs, and operative profiles are considered (cargo ship, passenger ship, and dredger). The technical and operational features of these ships are analyzed with an emphasis on their energy needs. Then, life-cycle assessments (LCAs) of a diesel engine-powered ship configuration and two battery-powered ship configurations (with and without a photovoltaic system) are performed by means of GREET 2020 software. These configurations are compared from the economical viewpoint, by the life-cycle cost assessment (LCCA), where potential carbon credit scenarios are investigated, while relevant quantities are converted into monetary units. Although the LCA identified the photovoltaic cells’ battery-powered ship configuration as the most environmentally friendly, according to the LCCA, its life-cycle costs are rather high, except for passenger ships, for which the battery-powered ship configuration is a feasible option. If a set of required specific input data is known, the presented procedure is applicable to reduce the environmental footprint of any other inland waterway fleet.